2021
DOI: 10.3389/fphar.2021.728458
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylureas for Treatment of Periodontitis-Diabetes Comorbidity-Related Complications: Killing Two Birds With One Stone

Abstract: Periodontitis is one of the most prevalent oral inflammatory diseases leading to teeth loss and oral health problems in adults. Periodontitis mainly affects periodontal tissue by affecting the host immune system and bone homeostasis. Moreover, periodontitis is associated with various systemic diseases. Diabetes is a metabolic disease with systemic effects. Both periodontitis and diabetes are common inflammatory diseases, and comorbidity of two diseases is linked to exacerbation of the pathophysiology of both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…21 It is believed that periodontitis and diabetes are related in a bidirectional manner. 22,23 Treatment modalities for periodontitis with T2DM are being explored. It is realized that effectively promoting alveolar bone regeneration in the inflammation resolution stage may provide a new perspective on periodontitis with T2DM treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 It is believed that periodontitis and diabetes are related in a bidirectional manner. 22,23 Treatment modalities for periodontitis with T2DM are being explored. It is realized that effectively promoting alveolar bone regeneration in the inflammation resolution stage may provide a new perspective on periodontitis with T2DM treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is an inflammatory disease that leads to inflammatory bone loss around teeth 21 . It is believed that periodontitis and diabetes are related in a bidirectional manner 22,23 . Treatment modalities for periodontitis with T2DM are being explored.…”
Section: Discussionmentioning
confidence: 99%
“…Another animal study using Zucker diabetic fatty rats report that GLP-1 RA promote osteoblastogenesis by attenuating the effect of advanced glycation endproducts (AGEs), oxidative stress and suppress bone resorption. A model of diabetic periodontitis in male Wistar rats report that administration of GLP-1 RA compared to saline increased BMD, trabecular thickness, trabecular number, and cortical thickness [27]. To illustrate the controversy of the evidence from animal studies on incretins and skeletal effects, a male Wistar rat model showed that treatment with a GLP-1 RA or a DPP4-i, which inhibits degradation of the GLP-1 molecule, reduced osteoclast function but could not revert osteoblast function and the impairment of bone strength in the diabetic state compared to controls [28].…”
Section: Preclinical Evidencementioning
confidence: 99%
“…Increase osteoblastogenesis, osteoblastic differentiation and bone formation [22,25,27] and may alleviate negative effects from hyperglycemia [23] May not be translated to humans fractures. This balance is illustrated in Fig.…”
Section: Glp-1mentioning
confidence: 99%
“…The results showed that insulin could improve inflammatory cell infiltration and expression of inflammatory cytokine genes and reduced the loss of alveolar bone. In addition, sulfonylurea drugs alleviate periodontitis possibly via direct mitigation of inflammation or indirectly via an antidiabetic effect [ 11 ]. Our previous experiments have also shown that hypoglycemic drug liraglutide (LIRA) can promote osteogenesis and inhibit the inflammatory reaction of human periodontal ligament cells (hPDLCs) stimulated by lipopolysaccharide, and confirm the therapeutic effect of LIRA on periodontitis in rats [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%